Oxytocin alleviates oxidative renal injury in pyelonephritic rats via a neutrophil-dependent mechanism - VELİOĞLU ÖĞÜNÇ, AYLİZ; YEGEN, BERRAK; ŞENER, GÖKSEL; ÇETİNEL, ŞULE (ELSEVIER SCIENCE INC, 2006)
Background: Urinary tract infection (UTI) may cause inflammation of the renal parenchyma and may lead to impairment in renal function and scar formation. Oxidant injury and reactive oxygen species (ROS) have been found responsible in the pathogenesis of UTI. The neurohypophyseal hormone oxytocin (OT) facilitates wound healing and is involved in the modulation of immune and inflammatory processes. We investigated the possible therapeutic effects of OT against Eschericia coli induced pyelonephritis in rats both in the acute and chronic setting. Methods: Twenty-four Wistar rats were injected 0.1 ml solution containing E. coli ATCC 25922 10(10) colony forming units/ml into left renal medullae. Six rats were designed as sham group and were given 0.1 ml 0.9% NaCl. Pyelonephritic rats were treated with either saline or OT immediately after surgery and at daily intervals. Half of the pyelonephritic rats were decapitated at the 24th hour of E. coli infection, and the rest were followed for 7 days. Renal function tests (urea, creatinine), systemic inflammation markers [lactate dehydrogenase (LDH) and tumor necrosis factor alpha (TNF-alpha)] and renal tissue malondialdehyde (MDA) as an end product of lipid peroxidation, glutathione (GSH) as an antioxidant parameter and myeloperoxidase (MPO) as an indirect index of neutrophil infiltration were studied. Results: Blood urea, creatinine, and TNF-a levels were increased, renal tissue MDA and MPO levels were elevated and GSH levels were decreased in both of the pyelonephritic (acute and chronic) rats. All of these parameters and elevation of LDH at the late phase were all reversed to normal levels by OT treatment. Conclusion: OT alleviates oxidant renal injury in pyelonephritic rats by its anti-oxidant actions and by preventing free radical damaging cascades that involves excessive infiltration of neutrophils. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: Eschericia coli; oxytocin; glutathione; lipid peroxidation; myeloperoxidase; TNF-alpha; ESCHERICHIA-COLI PYELONEPHRITIS; MEDIATED TISSUE-INJURY; REACTIVE OXYGEN; RETROGRADE PYELONEPHRITIS; GROWTH-HORMONE; INFLAMMATION; STRESS; KIDNEY; IMMUNIZATION; VASOPRESSIN